Independent Financial Expert Members on Audit Committees, Earnings Management and The Role of Female Directors - Anis Ben Amar; Nourhen Sayadi (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - What is the impact of the presence of expert and independent members within the audit committee on earnings management? What is the impact of the presence of expert and independent women on the audit committee on earnings management? Motivation - A number of studies have empirically examined the impact of audit committee financial expertise on earnings management. However, the results have been mixed (Ben Amar, 2014; Zalata et al., 2018). Some studies find a negative impact, while others find no significant association (eg. Yang & Krishnan, 2005). Moreover, examining all of this work allows us to observe an ongoing debate concerning the type of expertise that is most associated with earnings management. Idea - This paper examines the impact of independent financial expert members on the audit committee on earnings management. Moreover, the presence of female financial experts on the audit committee is necessary for the effectiveness of internal control mechanisms to mitigate earnings management. Hence, the impact of female financial experts on the audit committee on earnings management is also examined. Tools - This study uses a sample of 280 French non-financial companies listed on the CAC All Tradable index for the period 2008-2018. Feasible Generalized Least Square (FGLS) regression method is used to estimate the econometric models. Findings - Based on a panel of 3080 French firm-observations from 2008 to 2018 period, a negative effect of the audit committee's financial expertise on earnings management was observed. We also find that the proportion of female independent financial experts on the audit committee is significantly associated with less earnings management. Contribution - Our findings expand the literature on the relationship between audit committee structure and earnings management and provide guidance for regulatory bodies in some countries, due to the further integration of types of expertise related to audit committee members. Thus, regulators need to intensify their efforts on the optimal characteristics of this control mechanism.
Keywords: M41; M42; M48; 650; Earnings management; Audit committee; Financial expertise; Female directors; discretionary accruals; Real earnings management